2022
DOI: 10.1002/prot.26411
|View full text |Cite
|
Sign up to set email alerts
|

Total free energy analysis of fully hydrated proteins

Abstract: The total free energy of a hydrated biomolecule and its corresponding decomposition of energy and entropy provides detailed information about regions of thermodynamic stability or instability. The free energies of four hydrated globular proteins with different net charges are calculated from a molecular dynamics simulation, with the energy coming from the system Hamiltonian and entropy using multiscale cell correlation. Water is found to be most stable around anionic residues, intermediate around cationic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…The AMBER 14( Salomon-Ferrer et al, 2013 ) package with the AMBER force field FF99 ( Spasic et al, 2012 ) was also used to minimize, add counter ions, solvate, equilibrate, and run periodic box, explicit water (TIP4P) MD simulations for the best inhibitors. The protein–ligand-water system data analysis was carried out with the AMBER Tools distribution program ( Kalayan et al, 2023 , Kalayan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The AMBER 14( Salomon-Ferrer et al, 2013 ) package with the AMBER force field FF99 ( Spasic et al, 2012 ) was also used to minimize, add counter ions, solvate, equilibrate, and run periodic box, explicit water (TIP4P) MD simulations for the best inhibitors. The protein–ligand-water system data analysis was carried out with the AMBER Tools distribution program ( Kalayan et al, 2023 , Kalayan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier works questioning the thermodynamic explanation for water-protein interactions ( Watterson, 1997 ), and how solid-state physics could help understand the behavior of hydrated proteins ( Teeter et al, 2001 ), found some echo in recent publications. First, free energies analyzed for four hydrated globular proteins differing by their net charges revealed that water was most stable around anionic residues, and least stable near hydrophobic residues ( Kalayan et al, 2023 ). As most biomacromolecules fold into chiral structures for their biological functions, how water molecules rearrange to minimize free energy at interfaces was shown, with achiral water molecules assembling in the first hydration shell of the protein into a chiral supramolecular structure with chirality transferred from the protein ( Yan et al, 2023 ).…”
Section: Recent Breakthroughs On the Biophysics Of Water In The Cellmentioning
confidence: 99%
“…In EE-MCC the energy is taken from the MD simulations and the entropy is calculated for both solute and solvents over all degrees of freedom at multiple length scales. MCC has been developed for liquids, 29,30,32 solutions, [33][34][35][36] chemical reactions, 37 host-guest systems, 38 and proteins 31,[39][40][41] and offers the advantage of providing a comprehensive breakdown of entropy across all atomic degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%